Sources and resources ‘The People’s Chemists’: the Walgreens Boots Alliance Archive - Greenwood, Anna (Oxford University Press, 2018)
This article explores the historic records of the Walgreens Boots Alliance (WBA) Archive, a repository of over 500,000 items chronicling the over 165-year history of Britain’s most famous pharmaceutical retailer. It introduces some of the diverse materials present in the collection that would be of interest to social historians of medicine and pharmacy, particularly highlighting resources pertinent to understanding developments in: the formation of pharmaceutical identity; medical advertising; the internationalisation of pharmaceutical and medical retailing; product research and development; and employee welfare. In the light of the recent launch of the first phase of the Boots online catalogue, the article demonstrates ways in which these records could be utilised to better understand the wider social, cultural and political dynamics at play in the development of medicine, healthcare and pharmacy in Britain over the long twentieth century.